Long-Term Effects of Alemtuzumab on CD4+ Lymphocytes in Multiple Sclerosis Patients: A 72-Month Follow-Up - Rolla, Simona; De Mercanti, Stefania Federica; Bardina, Valentina; Maglione, Alessandro; Taverna, Daniela; Novelli, Francesco; Cocco, Eleonora; Vladic, Anton; Habek, Mario; Adamec, Ivan; Annovazzi, Pietro Osvaldo Luigi; Horakova, Dana; et al. (Frontiers in Immunology, 2022)
Introduction Alemtuzumab is highly effective in the treatment of patients with relapsing multiple sclerosis (PwRMS) and selectively targets the CD52 antigen, with a consequent profound lymphopenia, particularly of CD4+ T lymphocytes. However, the immunological basis of its long-term efficacy has not been clearly elucidated. Methods We followed up 29 alemtuzumab-treated RMS patients over a period of 72 months and studied the immunological reconstitution of their CD4+ T cell subsets by means of phenotypic and functional analysis and through mRNA-related molecule expression, comparing them to healthy subject (HS) values (rate 2:1). Results In patients receiving only two-course alemtuzumab, the percentage of CD4+ lymphocytes decreased and returned to basal levels only at month 48. Immune reconstitution of the CD4+ subsets was characterized by a significant increase (p < 0.001) in Treg cell percentage at month 24, when compared to baseline, and was accompanied by restoration of the Treg suppressor function that increased within a range from 2- to 6.5-fold compared to baseline and that persisted through to the end of the follow-up. Furthermore, a significant decrease in self-reactive myelin basic protein-specific Th17 (p < 0.0001) and Th1 (p < 0.05) cells reaching HS values was observed starting from month 12. There was a change in mRNA of cytokines, chemokines, and transcriptional factors related to Th17, Th1, and Treg cell subset changes, consequently suggesting a shift toward immunoregulation and a reduction of T cell recruitment to the central nervous system. Conclusions These data provide further insight into the mechanism that could contribute to the long-term 6-year persistence of the clinical effect of alemtuzumab on RMS disease activity.